Empathic Caring Consultation (ECC): Will It Be Able to Improve the Quality of Care at the Health Centers? - Prawitasari, Johana E.; Hadiwirawan, Olivia; Winarti, Hening Dwi Handayani Sri; Intriaty (ANIMA Indonesian Psychological Journal, 2010)
The purpose of this study is to support the evidence that ECC is effective to improve the quality of care in health centers in Sleman District, DIY, where myalgia complaints and the use of analgesics were high. ECC involves active listening, expressions of empathy, and short version of deep muscle relaxation. Method used was controlled trial design in 4 health centers. Two health centers were randomly assigned to the experimental and the control groups. Surveys of analgesics prescribing and the quality of care perceived by patients were conducted before and after the ECC. Results showed that there was no effect of ECC on the use of analgesics. Patients’ perception toward the quality of care in the experimental groups improved slightly. Health providers in the experimental groups showing more concern using nonverbal communication were perceived as more empathetic. They also referred more cases to the psychologists when needed. Tujuan penelitian ini adalah mendukung adanya bukti empiris bahwa Empathic Caring Consultation (ECC) sangkil untuk meningkatkan kualitas pelayanan di puskesmas di Kabupaten Sleman, DIY, di mana jumlah kasus mialgia dan penggunaan analgesika tinggi. ECC meliputi mendengarkan aktif, ungkapan empati, dan versi pendek ralaksasi otot. Metode yang digunakan adalah desain percobaan terkendali di 4 puskesmas. Dua puskesmas secara undian dipilih menjadi kelompok eksperimen dan kelompok kontrol. Survei peresepan analgesika dilakukan secara retrospektif tiga bulan sebelum dan sesudah ECC. Survei kualitas pelayanan dilakukan sebelum dan sesudah ECC diterapkan. Hasil penelitian menunjukkan bahwa tidak ada dampak ECC pada penggunaan analgesika di empat puskesmas yang diteliti. Persepsi pasien terhadap kualitas pelayanan di kelompok eksperimen meningkat sedikit. Petugas kesehatan di kelompok eksperimen, yang memperlihatkan perhatiannya melalui ungkapan nonverbal, dianggap lebih berempati. Mereka juga merujuk pada psikolog bila dibutuhkan.